SISTEM INFORMASI E-COMMERCE MENGGUNAKAN CMS WORDPRESS PADA TOKO IWAN MOTOR (TIM2SORE) DENGAN MENERAPKAN METODE RAD - Ilyas; Khairul Ihwan; Muhammad Amin; Muhammad Jibril (KARYA ABDI, 2022)
The development of IT today offers many conveniences in doing business. Tim2Store shop is one of the businesses in the field of selling two-wheeled vehicles. One of the obstacles is that sales problems are sometimes still one of the obstacles in achieving business goals, because the sales system is still done manually. To solve this problem, the author develops an electronic commerce using wordpress CMS. transactions are still carried out manually, the management of data dams is not yet structured and the lack of means of purchasing and paying online or through account transfers. Then built an Online Sales Information System at the Iwan Motor Shop (Tim2Srote) which will use the PHP programming language. With this system, it is hoped that it can help Iwan Motor Shop in marketing the sale of two-wheeled vehicles (motorcycles) online and quickly, so WordPress CMS is used. By applying the Rapid Application Development method to speed up preparation and shorter estimated time. And related to the problem of writing the Journal according to information obtained from Iwan Motor (Tim2store) Shop.